2014
DOI: 10.7314/apjcp.2014.15.9.4101
|View full text |Cite
|
Sign up to set email alerts
|

8-60hIPP5m-Induced G2/M Cell Cycle Arrest Involves Activation of ATM/p53/p21cip1/waf1Pathways and Delayed Cyclin B1 Nuclear Translocation

Abstract: Protein phosphatase 1 (PP1) is a major serine/threonine phosphatase that controls gene expression and cell cycle progression. The active mutant IPP5 (8-60hIPP5 m ), the latest member of the inhibitory molecules for PP1, has been shown to inhibit the growth of human cervix carcinoma cells (HeLa). In order to elucidate the underlying mechanisms, the present study assessed overexpression of 8-60hIPP5 m in HeLa cells. Flow cytometric and biochemical analyses showed that overexpression of 8-60hIPP5 m induced G2/M-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Alternatively, PVI and PVII activated p21 Waf1/Cip1, a cyclin‐dependent‐kinase inhibitor, which may inhibit the expression of cyclin B1 in NCI‐H1299 cells. The G2/M checkpoint prevents cells from entering mitosis when DNA is damaged; if the DNA damage is irreparable, checkpoint signaling might activate pathways that lead to apoptosis (Wang et al ., ; Zeng et al ., ). The results of the present study showed that PVI and PVII induced apoptosis in a dose‐dependent manner in A549 cells (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively, PVI and PVII activated p21 Waf1/Cip1, a cyclin‐dependent‐kinase inhibitor, which may inhibit the expression of cyclin B1 in NCI‐H1299 cells. The G2/M checkpoint prevents cells from entering mitosis when DNA is damaged; if the DNA damage is irreparable, checkpoint signaling might activate pathways that lead to apoptosis (Wang et al ., ; Zeng et al ., ). The results of the present study showed that PVI and PVII induced apoptosis in a dose‐dependent manner in A549 cells (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…When DNA double strand breaks (DSBs) occur, serine/threonine-specific kinase ATM is activated. ATM phosphorylates p53 and modulates p53/Cyclin B1-mediated G2/M phase arrest [4]. Checkpoint kinases Chk1 and Chk2, which undergo phosphorylation and activation by ATR and ATM, have a crucial function in regulating the G2 phase checkpoint and may serve as potential targets for radiotherapy [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Signals from the transducer to effector kinases are forwarded by mediator proteins such as Chk1, a Ser/Thr protein kinase which controls the G2/M phase transition in response to DNA damage. p53 (a tumor suppressor) activates p21 (a cyclin-dependent kinase inhibitor, which represents a major target of p53 activity), both of which have also been well established as critical mediators of cellular responses to DNA damage, apoptosis and cell cycle arrest (Becker et al, 2014; Zeng et al, 2014; Zhu et al, 2014). Therefore, we focused our attention on these checkpoint-related proteins.…”
Section: Resultsmentioning
confidence: 99%